Relevansi Teori-teori Belajar dan Pembelajaran dalam Perspektif Pendidikan dan Islam - Muhammad Nasron; Ai Siti Hodijah; Friti Sulastri; Rizki Febriansyah (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Understanding the processes of learning and teaching is essential in education. In the context of Islamic education, learning involves cognitive, spiritual, and moral aspects, requiring theories that align with its core values. Objective: This study aims to explore the concepts of learning and teaching and to understand various learning theories that support the educational process. Method: The research employs a library research method with an analytical approach to relevant literature. Result: The results indicate that learning and teaching are distinct yet interconnected concepts. Learning has specific characteristics and is influenced by various factors. Additionally, several major learning theories exist, including cognitivism, behaviorism, humanism, and constructivism. In the context of Islamic education, four learning theories are recognized: taqlid, tajribah wa khatha, ta’wid, and tafakkur. Conclusion: The study concludes that understanding learning theories is crucial for enhancing the effectiveness of teaching and learning processes. Contribution: The contribution of this research lies in providing a more comprehensive insight into learning concepts and theories that can be applied in various educational contexts, including Islamic education.